Inflammatory Modifications in Paranasal Sinuses and Ostiomeatal Complex Anatomical Variations in Jet Aircraft Pilots: A Computed Tomography Study - da Silva, Yeda; Munhoz, Luciana; Parga Filho, José Rodrigues; Damasceno, Andreza Gomes; Rosa, Cesar Felipe França da; Zukovski, Eduardo Bilaqui; Teng, Erik Zhu; Arita, Emiko Saito; Castro, Cláudio Campi de (International Archives of Otorhinolaryngology, 2023)
Introduction Jet aircraft pilots are exposed to huge pressure variation during flight, which affect physiological functions as systems, such as the respiratory system.Objectives The objective of the present investigation was to evaluate inflammatory changes of paranasal sinuses of jet aircraft pilots before and after a jet aircraft training program, using multislice computed tomography (CT), in comparison with a group of nonairborne individuals with the same age, sex, and physical health conditions. A second objective of the present study was to assess the association between the ostiomeatal complex obstruction and its anatomical variations.Methods The study group consisted of 15 jet aircraft pilots participating in the training program. The control group consisted of 41 nonairborne young adults. The 15 fighter pilots were evaluated before initiating the training program and after their final approval for the presence of inflammatory paranasal sinus disease. The ostiomeatal complex anatomical variations and obstructions were analyzed in pilots after the training program.Results Jet aircraft pilots presented higher incidence of mucosal thickening in maxillary sinus and anterior ethmoid cells than controls. Prominent ethmoidal bulla showed significant association with obstruction of the osteomeatal complex.Conclusions Jet aircraft pilots present increased inflammatory disease when compared with nonairborne individuals. The presence of a prominent ethmoidal bulla is associated with ostiomeatal complex obstruction.
Keywords: multidetector computed tomography; diagnostic imaging; maxillary sinus; aerospace medicine; aviation